I need a hug - Blabey, Aaron (New York : Scholastic Press, 2019)
A little porcupine just wants a hug, but all the other animals shy away from his prickly spikes--except for a snake.
"First published in Australia in 2015 by Scholastic Press, an imprint of Scholastic Australia Pty Ltd."--Copyright page.
Keywords: Porcupines -- Juvenile fiction; Animals -- Juvenile fiction; Hugging -- Juvenile fiction; Friendship -- Juvenile fiction; Stories in rhyme; Porcupines -- Fiction; Animals -- Fiction; Hugging -- Fiction; Friendship -- Fiction